Deployment of a Large-scale Peer-to-Peer Social Network - Yang, Mao; Chen, Hua; Zhao, Ben Y.; Dai, Yafei; Zhang, Zhengyou (USENIX, 2004)
We present the design and architecture of the Maze file-sharing and social network. Maze is one of the first large-scale deployments of an academic research project, with over 210,000 registered users and more than 10,000 users online at any time, sharing over 140 million files. Maze includes an evolving incentive structure, and simple mechanisms for providing network locality. We outline the Maze architecture and describe initial results from a measurement study.